Editorial Introduction - Catherine F. Compton-Lilly (Networks: An Online Journal for Teacher Research, 2014)
Welcome to Volume 16, Number 1 of Networks: An Online Journal for Teacher Research. I am thrilled to introduce you to another volume featuring the voices of educators. This issue includes articles focused on learning centers in first grade classrooms, mentoring teacher researchers, and the potential of reflective journaling for preservice teachers as well as a review of The Networked Teacher: How New Teachers Build Social Networks for Professional Support by Kira Baker-Doyle.